2021
DOI: 10.1136/tsaco-2020-000663
|View full text |Cite
|
Sign up to set email alerts
|

Balloons up: shorter time to angioembolization is associated with reduced mortality in patients with shock and complex pelvic fractures (original study)

Abstract: BackgroundAngioembolization has been the gold standard for management of pelvic arterial bleeding, but applicability has been limited by delays in access at many trauma centers. We hypothesized that a quality improvement program to reduce time to start of angiography would be associated with lower in-hospital mortality in patients with pelvic fractures and shock.MethodsRetrospective study of adults with a pelvic fracture and vital signs consistent with shock admitted to a level I trauma center after the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The overall decision-TAE time was 60 min, even after performing other resuscitation procedures. Although PPP may have advantages over TAE, namely that of early start time [7,12], most patients with pelvic fracture, even if they are unstable, can be managed with primary TAE strategies at centers that have 24-h availability of interventional radiologists [35].…”
Section: Discussionmentioning
confidence: 99%
“…The overall decision-TAE time was 60 min, even after performing other resuscitation procedures. Although PPP may have advantages over TAE, namely that of early start time [7,12], most patients with pelvic fracture, even if they are unstable, can be managed with primary TAE strategies at centers that have 24-h availability of interventional radiologists [35].…”
Section: Discussionmentioning
confidence: 99%
“…Unstable fracture patterns were defined as anterior posterior compression (APC) type 2/3, lateral compression 2/3, and vertical shear. 80 In the aforementioned AAST multicenter study, Constantini and colleagues 1 also found that APC 3 and open book pelvic fractures were significantly associated with intervention need.…”
Section: Angioembolization Rationalementioning
confidence: 96%
“…AE is indicated for the suspicion of an injured pelvic artery that is actively bleeding [37]. REBOA, a temporary hemostatic measure to control combined multiple arterial bleedings or damage of main artery, could be used to transport the hemorrhagic shock patients to the operation suite [10,44].…”
Section: The Mortalitymentioning
confidence: 99%
“…Endovascular intervention (EI), such as angiography-embolization (AE) and resuscitative endovascular balloon occlusion of the aorta (REBOA), recent years has been successfully used in hemostatic resuscitation [9]. Early angiography and subsequent embolization or balloon occlusion help to stop the arterial bleeding and displays a signi cant improvement in survival rate [10,11] .…”
Section: Introductionmentioning
confidence: 99%